Suis-je le gardien de mon frère ? Thérèse Raquin d'Émile Zola, une réécriture de Caïn et Abel - Holley, William Bradley (RELIEF - REVUE ÉLECTRONIQUE DE LITTÉRATURE FRANÇAISE, 2017)
Émile Zola’s Thérèse Raquin exemplifies what the author would develop as his naturalist philosophy. This philosophy, based upon what the Zola considered to be a scientific and empirical process to understand the human condition, appears at a time in France where many different philosophical thoughts converge. This paper looks at how Zola’s declared scientific study of the “human-beast” is in fact a retelling of the Biblical tale of Cain and Abel, perhaps spurred by the confusion of the competing philosophies.